Sosialisasi Penanganan Permasalahan Sistem Reproduksi Dan Infertilitas Pada Wanita Melalui Webinar - Sembiring, Julina; Kadir, Dalimawaty; Sukatendel, Khairani (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Disorders of the female reproductive organs can be caused by many things. If left untreated, some of these diseases of the female reproductive system can even increase a woman's risk of experiencing fertility problems. The female reproductive system consists of the labia majora, labia minora, Bartholin's glands, clitoris, vagina, uterus or uterus, ovaries (ovaries), and fallopian tube. The female reproductive system is a very complex body system, so steps are needed to protect this system from infection and injury. In addition, it is necessary to prevent problems that may occur in the female reproductive system, including long-term health problems. Maintaining the reproductive system is the same as maintaining personal health, especially during pregnancy. This service activity aims to increase public knowledge about the Handling of Reproductive System Problems and Infertility in Women. The method used is socialization through a webinar entitled